Do big data ao enunciado em This Person Does Not Exist: a questão da colocação em discurso - Médola, Ana Silvia Lopes Davi [UNESP]; Pereira, Henrique Da Silva [UNESP] (Programa de Estudos Pós-graduados em Comunicação e Semiótica - PUC-SP, 2024)
The article addresses the enunciation in the imagery of imagetic texts produced with the total or partial incorporation of artificial intelligence (AI) algorithms, focusing on how meaning is produced from the enunciative contracts established in the communication relationship. The theoretical-methodological basis of French discursive semiotics enables the analysis of the effects of meaning generated on the website This Person Does Not Exist, which manifests an imagery turning into text in which human faces are incessantly invented and presented to the user who browses the Internet through the use of AI algorithms. The study examines the articulation between human and machine enunciation actors in the placement in discourse. It was observed that the human actor plays inchoative roles in the procedures of making discourse, since it is the primary source of the organization of the big data and the programming of the matrix algorithm that triggers the automation carried out a posteriori by the machine actor that produces the synthetic images, represented by the GAN algorithm, and articulates different languages for the establishment of the enunciative contract.

O artigo aborda a enunciação em textos imagéticos produzidos com a incorporação total ou parcial de algoritmos de inteligência artificial (IA), concentrando-se na maneira como o sentido é produzido a partir dos contratos enunciativos estabelecidos na relação de comunicação. A base teórico-metodológica da semiótica discursiva de linha francesa possibilita a análise dos efeitos de sentido gerados no site This Person Does Not Exist, que manifesta uma textualização imagética na qual rostos humanos são incessantemente inventados por meio da utilização de algoritmos de IA e apresentados ao usuário que navega na internet. O estudo examina a articulação entre os atores da enunciação humano e maquínico na colocação em discurso. Observou-se que o ator humano cumpre papéis incoativos nos procedimentos de discursivização, uma vez que é fonte primária da organização do big data e da programação do algoritmo matriz que desencadeia a automação realizada a posteriori pelo ator maquínico que produz as imagens sintéticas, representado pelo algoritmo GAN, e articula diferentes linguagens para o estabelecimento do contrato enunciativo.
From big data to enunciation in This Person Does Not Exist: the issue of discourse placement
Keywords: artificial intelligence; This Person Does Not Exist; enunciation; semiotics; inteligência artificial; This Person Does Not Exist; enunciação; semiótica